Combined effect of light harvesting strings, anti‐reflective coating, thin glass, and high ultraviolet transmission encapsulant to reduce optical losses in solar modules. (3rd February 2014) - Schneider, Jens; Turek, Marko; Dyrba, Marcel; Baumann, Ihno; Koll, Bernd; Booz, Thomas
ABSTRACT Optical losses are a major source for current and power reduction in solar modules. Hence, various improvements aiming at reducing these losses have been suggested. In this work, we have evaluated the effects of anti‐reflective coating, front glass thickness, polyvinyl butyral ultraviolet+ encapsulant, and light harvesting strings on the module performance individually and in combination. The individual and combined contributions were quantified by spectrally resolved optical measurements on the module components and simulations as well as electrical measurements on 1‐cell and 54‐cell modules. Optical gains and their impact on short circuit current are discussed in relation to a maximum current obtained from the solar cells internal quantum efficiency. The results of the electrical characterization are in good agreement with the optical analysis substantiating our approach. They show that a combined, relative current enhancement of 5% can be obtained for an optimized module, which compares to an increase of 1% absolute efficiency. Copyright © 2014 John Wiley & Sons, Ltd.